ANALISIS PERKEMBANGAN INTEGRASI EKONOMI ASEAN MENUJU PEMBERLAKUAN ASEAN ECONOMIC COMMUNITY (AEC) TAHUN 2015 - YUNITA, PRIMADIANA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The aim of this research is to explain the reason why ASEAN still do the economic integration through ASEAN Economic Community in 2015 although the prerequisite as economic community has not been fulfilled. In order to explain the focus of this research, the researcher used identity concept which is proposed by Amitav Acharya. This identity concept is meant to explain that a country's involvement and allegiance in a regional integration if it is not based on material use which can be determined systematically, Therefore, based on the identity arrangement developing in ASEAN countries make an agreement to reach a common goal. This research uses qualitative method as the analysis technique through data collection from literature review. The result shows that ASEAN Economic Community does not provide material change towards every country of ASEAN members. However ASSEAN can strengthen its collective identity through economic integration which is done through several agreements and economic cooperation for goods and services.